The vitamins : fundamental aspects in nutrition and health - Combs, Gerald F. (Elsevier, 2012)
Provides advanced coverage of the biochemistry and physiology of vitamins and vitamin-like substances. Suitable for those interested in nutrition, food science, animal science or endocrinology, this title provides a presentation of each of the vitamins, as well as the history of their discoveries and information about their roles in nutrition